Antecedents to Intention to Engage in the Online Negative Word-of-Mouth Communication - Dien Mardhiyah; Basu Swastha Dharmmesta; B. M. Purwanto (Gadjah Mada International Journal of Business, 2013)
Complaints delivered directly to a firm will not be a problem if they can be handled properly, while the ones that are not disclosed directly to the firm but to a third party or even warnings to others not to use particular products or services, will be negative word-of-mouth communication. It can damage the image of the firm and be very detrimental. The purpose of this study was to analyze the antecedents of intention to engage in negative online word-of-mouth communication that includes dissatisfaction, service importance, success of complaint, complaint benefit, self confidence, altruism, retaliatory intention, and complaint cost. Medical services were selected considering the impact caused by the negligence of the service provider possibly giving rise to negative word-of-mouth communication. The online environment has been considered because of the developments in technology which provide opportunities for consumers to communicate with ach other. In addition, the dissemination of information through online media can spread incredibly widely and rapidly. The samples in this study comprised consumers of medical services who had disappointing experiences in using those services either directly or indirectly. A total of 123 questionnaires were analyzed with multiple regression analysis to test the research hypothesis. The results showed that the factors influencing the intentions behind negative online word-of-mouth communication were success of complaint, altruism, retaliatory intention, and complaint cost.